Managing the shortage: A quantitative-qualitative study on the scale and effects of the severe lack in sign language interpreting resource in the German market - Laura Marie Maaß (VAKKI Publications)
This study provides an insight into the extent of the shortage of sign language interpreters in Germany and the impact this has on the co-operation and workflows between hearing sign language interpreters and their deaf clients. There is a considerable lack in sign language interpreters in Germany; on average, each deaf person can only receive around 18 hours of interpreting services per year. In the context of growing demands for participation and inclusion, for example in education, and the accessibility of events of all kinds, we see a growing tension between the two groups. With almost 800 respondents, this study provides insight in the relationship between hearing sign language interpreters and their deaf clients. It focusses on various application scenarios and shows, among other things, that the shortage is currently reflected in the area of acute medical emergencies and that the current free market will not cover this shortage.